Top management group heterogeneity and firm performance - Murray, Alan (Strategic Management Journal, 1989)
Using a sample of 84 Fortune 500 food and oil companies, observed over the period 1967 to 1981, this paper tests a number of hypotheses relating top management group composition to firm performance. Specifically, it was expected that homogeneous top management groups would interact more efficiently and therefore be preferable when competition is intense, but that heterogeneous groups would facilitate adaptation and therefore be preferable under conditions of environmental change. Partial support for these hypotheses was found; however, the pattern of results also highlights the numerous difficulties in untangling and identifying the determinants of firm performance.